Etude de l’efficacité de l’huile de Thevetia neriifolia pour le contrôle de Anopheles gambiae S.L résistant aux pyréthrinoïdes. - AKPO, Armand A.; CHOUGOUROU, CHÈPO DANIEL; DOSSOU, JOSEPH; AKOGBETO, CODJO MARTIN (My University, 2017)
Effective control of pyrethroid-resistant malaria vectors requires new alternative measures. The purpose of this study is to test the effectiveness of Thevetia oil extracted from seed kernels to control malaria transmission by An. gambiae s.l. Sensitivity tests were carried out on larvae of Stages 3 and 4 of An. gambiae s.s of wild-type and pyrethroid-resistant Kis-kdr. The susceptible reference strain "Kisumu" served as a control. Mortality was read 24 hours and 48 hours after exposure. LD50 and 90 for 24 hours and 48 hours were determined using the log-probit method of determining the dose corresponding to a proportion. The high LD50s determined in 24 hours and 48 hours correspond to doses that kill 50% of Stage 3 larvae in wild populations in 24 hours and 48 hours. Low LD50s refer to stage 4 "Kisumu" larvae. The strong DL90 in 24 hours and 48 hours correspond respectively to stage 3 larvae of the Kis-kdr and wild-type strains. The comparison of the LD between the different strains shows the influence of the resistance on the sensitivity of the larvae of the strains resistant to the oil tested. However, the larvicidal effect of Thevetia oil on the larvae of resistant strains may elicit formulations for alternative measures in vector resistance management to pyrethroids.
Keywords: Larvicidal activity; susceptibility test; An. gambiae s.s resistant; Anti - vector control